Transparency and Reform of Music Royalty Distribution in Indonesia, Australia, and the United States - Jayanti, Ni Putu Nita Anggrelia; Mahadewi, Kadek Julia (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The protection of economic rights for songwriters and musicians in Indonesia is regulated under Law No. 28 of 2014 on Copyright and Government Regulation No. 56 of 2021 on royalty management. However, implementation through the National Collective Management Institution (LMKN) still suffers from weak transparency, accountability, and data integration. This study analyzes the transparency of Indonesia’s royalty distribution system, compares it with practices in Australia and the United States, and proposes reform strategies. Using a normative legal research method with statute, conceptual, and comparative approaches, this research examines primary legal sources, academic works, and institutional reports. The findings reveal Indonesia lacks an integrated database, detailed audits, and independent supervision, causing legal uncertainty and eroding creators’ trust. By contrast, Australia’s APRA AMCOS and the U.S. system through ASCAP, BMI, SESAC, and the Mechanical Licensing Collective (MLC) offer greater transparency via digital monitoring, open annual reports, and strict regulatory oversight. These mechanisms enable creators to trace royalty flows and secure fair compensation. The study concludes that Indonesia requires comprehensive reform through digitalization, a national database, transparent reporting, and stronger independent monitoring to achieve a fair and accountable royalty distribution system.